Pengaruh Penambahan Fin Pada Sudu Terhadap Cut In Speed Turbin Angin Savonius Tipe L - Deny Prabowo; Danar Susilo Wijayanto; Indah Widiastuti (Universitas Janabadra, 2017)
This research aims to analyze the influence of additioning fin on blade of the cut in speed by a savonius wind turbine type L with variation of wind speed. This research used a savonius wind turbine type L with a rotor diameter of 1.1 m and a rotor height of 1.4 m. The method used is the experimental method by varying the addition of the fin on blade and the wind speed. Variables taken in this research are wind speed, variation of additioning fin, and cut in speed by wind turbine. Variations of additioning fin are without fin, 1 fin, 2 fin, 3 fin, 4 fin. Testing tools using anemometer. The results of the research was found that the additioning fin affect the cut in speed with the number of fin in the blade is linearly result in increasing ot the cut in speed. The lowest cut in speed is 2 m/s achieved the addition of 4 fin on the blade.